2012
DOI: 10.17305/bjbms.2012.2448
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil factor 3 isolated from human breast milk downregulates cytokines (IL8 and IL6) and promotes human beta defensin (hBD2 and hBD4) expression in intestinal epithelial cells HT-29

Abstract: Trefoil factors (TFF) are secretory products of mucin producing cells. Th ey play a key role in the maintenance of the surface integrity of oral mucosa and enhance healing of the gastrointestinal mucosa by a process called restitution. TFF comprises the gastric peptides (TFF), spasmolytic peptide (TFF), and the intestinal trefoil factor (TFF). Th ey have an important and necessary role in epithelial restitution within the gastrointestinal tract. Signifi cant amounts of TFF are present in human milk. Th is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…Interestingly, ITF not only promoted cell proliferation and migration, but also special physical function; for example, it helped to stabilize the mucus layer by binding to mucous glycoprotein (14,15). Additionally, experiments have shown that ITF plays an important role in protecting the integrity of the intestinal mucosa and promoting its reconstruction after injury (16)(17)(18)(19). Mice lacking ITF did not heal well after mucosa injury.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ITF not only promoted cell proliferation and migration, but also special physical function; for example, it helped to stabilize the mucus layer by binding to mucous glycoprotein (14,15). Additionally, experiments have shown that ITF plays an important role in protecting the integrity of the intestinal mucosa and promoting its reconstruction after injury (16)(17)(18)(19). Mice lacking ITF did not heal well after mucosa injury.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat necrotizing enterocolitis model, TFF3 improves inflammation by inhibiting the increase of Nf-κb, Il-1β, and Il-6, while enhancing the expression of Il-10, an anti-inflammatory cytokine (141). TFF3 inhibits IL-6 and IL-8 secretion induced by LPS and stimulates defensin production in the HT29 cell line in vitro (142). In addition to dampening pro-inflammatory cytokine amounts, TFF peptides themselves have been demonstrated to be regulated by cytokines or TLR signaling.…”
Section: Trefoil Factor and Gastrointestinal Diseasesmentioning
confidence: 99%
“…Purifi ed TFF3 was subjected to electrophoresis on 15 % SDS-PAGE and immunoblotting as previously reported (3).…”
Section: Sds-page and Immunoblottingmentioning
confidence: 99%
“…Membranes were washed 5 times with PBS-tween, blocked for 2 hours in 5 % skim milk in PBS-Tween, and incubated with 10 μg/ml of TFF3 (bait protein) in binding buffer (100 mMNaCl, 20 mMTris (pH 7.6), 0.5 mM EDTA, 10 % glycerol, 0.1 % Tween-20, 2 % skim milk powder) overnight at 4 °C. Bound TFF3 (bait protein) was detected by a primary antibody in a method similar to standard Immunoblotting described above (3). Membranes were stripped and were reprobed (the reprobed was done using standard immunobloting to determine the position of the PAR-2 (prey proteins) on the membrane).…”
Section: Far Western-blotmentioning
confidence: 99%
See 1 more Smart Citation